Lifestyle and youthful looks3. (15th April 2015) - Gunn, D.A.; Dick, J.L.; van Heemst, D.; Griffiths, C.E.M.; Tomlin, C.C.; Murray, P.G.; Griffiths, T.W.; Ogden, S.; Mayes, A.E.; Westendorp, R.G.J.; Slagboom, P.E.; de Craen, A.J.M.
Summary Background Lifestyle has been proven to have a dramatic effect on the risk of age‐related diseases. The association of lifestyle and facial ageing has been less well studied. Objectives To identify lifestyle factors that associate with perceived facial age in white north European men and women. Methods Lifestyle, facial wrinkling and perceived facial age were studied in two cross‐sectional studies consisting of 318 Dutch men and 329 women aged 45–75 years who were part of the Leiden Longevity Study, and 162 English women aged 45–75 years who were nonsmokers. Results In Dutch men, smoking, having skin that went red in the sun, being outside in the sun most of the summer, sunbed use, wearing false teeth and not flossing teeth were all significantly associated (P < 0·05) with a total 9·3‐year higher perceived facial age in a multivariate model adjusting for chronological age. In Dutch women, smoking, sunbathing, sunbed use, few remaining teeth and a low body mass index (BMI) were associated with a total 10·9‐year higher perceived facial age. In English women, cleaning teeth only once a day, wearing false teeth, irregular skin moisturization and having skin that went red in the sun were associated with a total 9·1‐year higher perceived facial age. Smoking and sunbed use were associated more strongly with wrinkling in women than in men. BMI, sun exposure and skincare were associated predominantly with perceived facial age via wrinkling, whereas oral care was associated via other facial features. Conclusions Although associative in nature, these results support the notion that lifestyle factors can have long‐term beneficial effects on youthful looks.